SO2-generating pads reduce gray mold in clamshell-packaged ‘Rubi’ table grapes grown under a two-cropping per year system - Débora Thaís Mühlbeier; Luana Tainá Ribeiro; Maíra Tiaki Higuchi; Youssef Khamis; Osmar José Chaves Junior; Renata Koyama; Sergio Ruffo Roberto (Semina: Ciências Agrárias, 2021)
The aim of this work was to evaluate different SO2-generating pads and liners to control gray mold in ventilated clamshell-packaged ‘Rubi’ table grapes grown under a two-cropping per year system. The treatments consisted of SO2-generating pads (slow release or dual release) and plastic liners with different perforations (microperforated; 2.0; 4.0 or 5.0 mm in diameter) and a control, only with the standard microperforated plastic liner. The packaged grapes were stored in a cold chamber at 1.0 ± 1.0 °C and 95% relative humidity. After 45 days, the grapes were removed from cold storage and placed, without liners and SO2-generating pads, for 3 days at room temperature (22.0 ± 1.0 °C). The evaluations occurred at 30 and 45 days after the beginning of cold storage, and the following variables were assessed: incidence of gray mold, mass loss, stem browning and shattered berries. At 3 days of shelf-life, the same variables were assessed, except mass loss. The completely randomized design was used as a statistical model with four replications, and each plot consisted of five bunches individually stored in ventilated clamshell-packaged. The dual release SO2-generating pads are efficient in controlling the gray mold in ‘Rubi’ table grapes regardless of the type of perforation of the plastic liners, with low mass loss and shattered berries, with good conservation of the freshness of the rachis. The disease was efficiently controlled in both annual crops. The slow-release SO2-generating pads, regardless of the type of perforation of the plastic liners, resulted in intermediate efficiency of gray mold control, with good physical quality of the bunches. Thus, the use of dual release SO2-generating pads is recommended to control gray mold in ventilated clamshell-packaged ‘Rubi’ table grapes.